Systemic lupus erythematosus, lupus nephritis and end-stage renal disease: a pragmatic review mapping disease severity and progression. (August 2020) - Mahajan, Anadi; Amelio, Justyna; Gairy, Kerry; Kaur, Gavneet; Levy, Roger A; Roth, David; Bass, Damon
Objective: The understanding of systemic lupus erythematosus (SLE) and lupus nephritis (LN) pathogenesis remains incomplete. This review assessed LN development in SLE, within-LN progression and progression to end-stage renal disease (ESRD). Methods: A keyword-based literature search was conducted, and 26 publications were included. Results: Overall, 7–31% of patients had LN at SLE diagnosis; 31–48% developed LN after SLE diagnosis, most within 5 years. Class IV was the most commonly found LN class and had the worst prognosis. Histological transformation occurred in 40–76% of patients, more frequently from non-proliferative rather than proliferative lesions. Cumulative 5- and 10-year ESRD incidences in patients with SLE were 3% and 4%, respectively, and 3–11% and 6–19%, respectively, in patients with SLE and LN. Conclusions: Elevated serum creatinine was identified as a predictor of worsening disease state, and progression within LN classes and from SLE/LN to ESRD. This review highlights the substantial risk for developing LN and progressing to ESRD amongst patients with SLE.